Characterization of a Lytic Bacteriophage vB_SurP-PSU3 Infecting Staphylococcus ureilyticus and Its Efficacy Against Biofilm - Kwon, Hyemin; Park, Seon Young; Kim, Min-Soo; Kim, Sang Guen; Park, Se Chang; Kim, Ji Hyung (Frontiers in Microbiology, 2022)
In response to the increasing nosocomial infections caused by antibiotic-resistant coagulase-negative staphylococci (CoNS), bacteriophages have emerged as an alternative to antibiotics. Staphylococcus ureilyticus, one of the species containing CoNS, has emerged as a pathogen of nosocomial infections that cause bloodstream infections. In this study, we have isolated and characterized a novel bacteriophage, vB_SurP-PSU3, that infects S. ureilyticus, and have demonstrated via host range analysis that the phage can simultaneously infect S. warneri. The isolated phage vB_SurP-PSU3 efficiently inhibited the growth of S. ureilyticus and prevented and degraded bacterial biofilms. Morphological characteristics and a genome-based phylogenic analysis revealed that phage vB_SurP-PSU3 belonged to the genus Andhravirus, and its overall genomic arrangement and contents were similar to those of other members of the Andhravirus. However, an additional comparative genome analysis demonstrated that the predicted endolysin of vB_SurP-PSU3 differed distinctly from the other members of the Andhravirus. Based on these findings, vB_SurP-PSU3 can be used as an efficient biological control agent against infections caused by S. ureilyticus biofilm.